Mosby's pocket dictionary of medicine, nursing, & allied health (Mosby, 2002)
The revised and updated New Edition distills all of the essential information from Mosby's Medical, Nursing, & Allied Health Dictionary, 6th Edition. It's still the only the only pocket-sized dictionary with a strong emphasis on nursing terminology. Comprehensive, compact, and affordable, it includes 3,000 new definitions (with 10,000 revised definitions), word roots and pronunciations for many entries, screened thumb tabs, and much more.